Tuberculosis treatment without rifampin in kidney/kidney–pancreas transplantation: A case series report. Issue 6 (14th December 2022) - Radisic, Marcelo Victor; Pujato, Natalia Rosana; Bravo, Pablo Martin; del Grosso, Roxana Constanza; Hunter, Martin; Beltramino, Santiago; Linares González, Laura; Cornet, María Lucía; del Carmen Rial, Maria; Franzini, Rosa Livia; Dotta, Ana C.; León, Luis Roberto; et al.
Abstract: Background: The best approach to tuberculosis (TB) treatment in transplanted patients is still unknown. Current guidelines are based on evidence either extrapolated from other populations or observational. Rifampin‐containing regimens have strong pharmacokinetic interactions with immunosuppressive regimens, with high rates of organ dysfunction and ∼20% mortality. This report describes the results obtained using non‐rifampin‐containing regimens to treat confirmed TB in adult patients with kidney/kidney–pancreas transplantation. Methods: Retrospective data analysis from confirmed TB cases in adult kidney/kidney–pancreas transplant recipients (2006–2019), treated "de novo" with non‐rifampin‐containing regimens. Results: Fifty‐seven patients had confirmed TB. Thirty patients were treated "de novo" with non‐rifampin‐containing regimens. These patients' mean age was 49.24 (±11.50) years. Induction immunosuppression was used in 22 patients. Maintenance immunosuppression was tacrolimus–mycophenolate–steroids in 13 (43%), sirolimus–mycophenolate–steroids in 6 (20%), and other immunosuppressive regimens in 11 (36%). Belatacept was used in four patients. TB localizations: pulmonary 43%; disseminated 23%; extrapulmonary 33%. Twenty‐seven (90%) patients completed treatment with isoniazid, ethambutol, and levofloxacin (12 months, 23; 9 months, 3; 6 months, 1); 12 of these patients also received pyrazinamide for the first 2 months and were cured with functioning grafts. One patient (3%) lost the graft while on treatment. Two patients (7%) died while on TB treatment. Median (range) follow‐up after completion of TB treatment was 32 (8–150) months. No TB relapses were observed. Conclusions: Results with non‐rifampin‐containing TB treatments in this case series were better (in terms of mortality and graft dysfunction) than those previously described with rifampin‐containing regimens in transplanted patients. Abstract : Tuberculosis treatment without rifampin in kidney/kidney pancreas transplantation.